2017
DOI: 10.15761/ams.1000130
|View full text |Cite
|
Sign up to set email alerts
|

Degradation study of used polystyrene with UV irradiation

Abstract: Keeping in view the growing concern regarding polymer degradation, the present study was undertaken with the view to study the effect of UV irradiation on degradation of used polystyrene. Polystyrene was collected from TV and computer packing. It was peeled into pieces and dissolved in toluene. The viscosity measurement was made according to the well reported standard method. The polystyrene sample was irradiated with UV irradiations having wavelength range of 365 nm. The irradiated polystyrene samples were ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 13 publications
1
9
0
1
Order By: Relevance
“…Concurrently, these reactions led to the formation of several new bands in the carbonyl region between 1650 and 1800 cm –1 , as illustrated in Figure a. Some of these bands have been identified in previous studies on the photodegradation of PS. ,,,,,,,− The 2D-COS asynchronous plot was used to deconvolute and identify CO bands between 1650 and 1800 cm –1 (Figure b). Several bands were identified, including 1654, 1665, 1674–1677, 1684, 1694, 1701, 1709, 1714–1717, 1720, 1728–1732, 1742–1744, 1751, 1757, 1760, 1770, 1774–1778, 1780, 1783–1786, 1791, and 1798 cm –1 .…”
Section: Resultsmentioning
confidence: 74%
“…Concurrently, these reactions led to the formation of several new bands in the carbonyl region between 1650 and 1800 cm –1 , as illustrated in Figure a. Some of these bands have been identified in previous studies on the photodegradation of PS. ,,,,,,,− The 2D-COS asynchronous plot was used to deconvolute and identify CO bands between 1650 and 1800 cm –1 (Figure b). Several bands were identified, including 1654, 1665, 1674–1677, 1684, 1694, 1701, 1709, 1714–1717, 1720, 1728–1732, 1742–1744, 1751, 1757, 1760, 1770, 1774–1778, 1780, 1783–1786, 1791, and 1798 cm –1 .…”
Section: Resultsmentioning
confidence: 74%
“…Biofilms can modify particles' vertical transport, potentially promoting the permanence of microplastics at intermediate depths [66]. Solar radiation, high in the SML [1,6] can modify particles' density and buoyancy; exposure to UV light can initiate the photo-oxidative degradation of plastics [67], while absorption of visible light (400-700 nm) accelerates their thermal degradation [68]. Moreover, solar radiation also promotes the emission of methane and ethylene from low-density plastics such as polyethylene, in particular when these plastics are exposed to air rather than completely submerged in water [69].…”
Section: Discussionmentioning
confidence: 99%
“…It is generally not accepted in curbside programs. Expanded polystyrene foam takes 900 years to decompose in the environment and has been documented to cause starvation in birds and other marine wildlife [39].…”
Section: Polystyrenementioning
confidence: 99%
“…Shah et al [39] have observed that the UV-irradiation having wavelength range of 365 nm has a profound effect on polystyrene sample. The reduction of the molecular weight of polystyrene shows the degradation of polystyrene macromolecules by irradiation.…”
Section: Polystyrenementioning
confidence: 99%